Capnocytophaga sputigena bacteremia in a neutropenic host (2019)
ABSTRACT: Capnocytophaga species belong to the oral microbiota but are not a common cause of infection in febrile neutropenia. Nevertheless, neutropenia can cause bacteremia associated with mucositis, with lower rates of mortality. While empirical therapy with beta-lactams is generally effective, there is concern about the emergence of bacterial resistance. We present a case of a febrile neutropenic patient with mucositis presenting with C. sputigena bacteremia.